MANAJEMEN SUMBER DAYA MANUSIA TENAGA ADMINISTRASI SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMK FAVORIT PUNGGING KABUPATEN MOJOKERTO - Syafaat, Wahyu (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2020)
Abstract School Administration Staff are educational staff who play an important role in improving school administration services. Therefore, the school administrative staff must have adequate competence in order to be able to carry out their duties and functions according to their competencies very professionally. Therefore it is necessary to have competency standards that must be possessed by administrative staff, especially in the field of digital literacy as a basis for competence in carrying out these tasks and functions. In educational institutions, especially the private sector, there are still many School Administration Staff who are still considered lacking in standard competency as a competent administrative staff, one of the reasons is because educational institutions recruit more administrative staff because of the kinship element where they are close people in these institutions without going through selection with clear competency standards, so that often the competency standards that need to be possessed by an administrative staff are neglected, consequently the quality of education services in schools is less than optimal. One effort to improve the ability of administrative staff in carrying out their daily tasks and functions in addition to the need for clear work guidelines and schools must also provide adequate facilities to improve the human resources of school administration staff in the form of adequate infrastructure as well as through training funded by the agency. The purpose of this study was to determine how big the role of school administration staff in the Vocational High School â€œFavoritâ€ Pungging Mojokerto in improving the quality of education in schools. The research method used in this study is qualitative research. The results of this study indicate that the management of human resources in school administration is very important and influential in improving the quality of education at the Vocational High School â€œFavoritâ€ Pungging Mojokerto.